Sustainable Business Innovation in Indonesian Firms ESG Disclosure Profitability and Greenwashing - Ferli, Ossi; Achsani, Noer Azam; Andati, Trias; Asikin, Zenal (Pandawan, 2026)
This paper aims to investigate the relationships among ESG disclosure score and profitability. The sample consist of sustainable companies in Indonesia, based on the Sustainalytics and Bloomberg databases. Panel regression analysis was employed to test the study hypotheses. The results indicate that ESG disclosure has a negative effect on firm profitability. Specifically, environmental and governance disclosures are negatively associated with profitability. Moreover, both the combined ESG score and the Squared ESG variable exhibit a negative effect on profitability. Net sales show a positive effect on profitability across all models. In contrast, the COVID-19 period was found to reduce firm profitability. This study is limited by the number of samples due to data availability, yet it provides implications for stakeholders by offering insights into how ESG disclosure influences profitability in the long term, particularly in the context of sustainability practices within developing countries. The findings also have significant implications for policymakers, firms, and investors, as these findings offer guidance on managing ESG disclosure to support financial performance while mitigating greenwashing effects. Finally, this study raises a critical question about whether ESG compliance and standards will remain instruments for capital market stakeholders or evolve into a transformative paradigm that reshapes stakeholder behaviour. This research contributes to the growing body of literature exploring the relationship between ESG disclosure and profitability by employing a self-developed index from annual report content analysis, thus providing a localized perspective on sustainability performance. Furthermore, it complements the literature on the non-linear relationship between sustainability and profitability.